Status of Wetland Birds in Chitwan National Park, Nepal - Jha, Praveen Kumar; Sharma, Chetan Kumar (Tribhuvan University Journal, 2018)
The study on status of wetland birds in Chitwan National Park was carried out from February 5, 2014 to February 20, 2014. The study aimed to determine status and distribution pattern of wetland birds in Chitwan National Park. Study area was divided into four sectors viz; Sunachari to Sauraha, Sauraha to Kasara, Kasara to Rapti/Narayani confluence,and Rapti/Narayani confluence to Tribeni. The total number of wetland birds recorded in the study area was 36 species. Out of them, 15 were winter migratory birds belonging to 5 families, and 21 were residents belonging to 9 families. Among them, Ruddy Shelduck (Tadorna ferruginea) was the most abundant species. Mainly fish-eating bird species were observed at river confluences and shaded forest areas. It was noted that wetland birds are decreasing in number due to high anthropogenic disturbances such as massive sand mining, habitat loss, over fishing, livestock grazing, use of poisoning in wetlands, water pollution, mass tourist pressure in the park and proliferation of alien invasive species.